(untitled) (Journal of Medical & Health Sciences Review, 2025)
Objective: To assess the contrast sensitivity and color vision among smokers and non-smokers. Methodology: It was a comparative cross-sectional study, conducted on 80 smokers and 80 non-smokers from January 2023- June 2023. Subjects were evaluated in the university of Lahore optometry lab and The University of Lahore Teaching Hospital. Color vision and contrast sensitivity were assessed by using the D15 test and Pelli-Robson chart. The selected age group was 20 to 40 years. The smoking limit was 10-20 cigarettes per day. Results: out of 160 participants, 80 (50%) smokers and 80 (50%) were non-smokers. Contrast sensitivity of smokers was found, a maximum of 2.25 (50%) and a minimum of 1.65 (0.6%) while among non-smokers contrast sensitivity was a maximum of 2.25 (48.1%) and a minimum of 1.65 (0.6%) having P-value of 0.153. Evaluation of color vision among smokers showed normal (32.5%), Protanopia (0.6%), Deuteranopia (50%), and Tritanopia (11.25%). Colour vision of non-smokers gives us normal (46.9%), Deuteranopia (50%) and Tritanopia (2.5%) with a P-value of 0.006. Conclusion: It was concluded that excessive smoking affects color vision more and contrast sensitivity to a lesser extent. The P-value shows a statistically significant association between color vision deficiency in smokers and an insignificant association of contrast sensitivity.